STANDARISASI SPESIFIK DAN NON SPESIFIK EKSTRAK ETIL ASETAT DAUN DANDANG GENDIS (Clinacanthus nutans) - Sholikhah Deti Andasari; Choiril Hana Mustofa; Shofia zahra (MOTORIK Jurnal Ilmu Kesehatan, 2020)
The leaves of dandang gendis (Clinacanthus nutans) have several pharmacological activities including antioxidants, anticancer, anti-inflammatory, analgesic, immune system boosting, antibacterial, antiviral, anti-venom (scorpion), and there is even cosmetic use. The purpose of this research was to see the test results for specific and non-specific parameters of the ethyl acetate extract of dandang gendis leaves (Clinacanthus nutans).This research is descriptive quantitative in nature and was carried out in an experimental laboratory. This research began with the maceration of 500 grams of dandang gendis leaf powder using 2000 ml ethyl acetate solvent while stirring every 24 hours, filtered with a flannel cloth, and evaporated until thick with a water bath. The parameters tested were the identity of the extract, organoleptic, parameters of air and ethanol dissolved compounds, chemical content of the extract, determination of air content, determination of drying losses, and specific gravity.The results showed that the ethyl acetate extract of dandang gendis leaves with the expression of the extract in the form of a thick extract, blackish green color, bitter taste, and characteristic aromatic odor; ethanol soluble compound content 21.881% ± 1.256; air-soluble compound content 21.959% ± 0.992; the chemical group indication indicates the presence of flavonoids, tannins and saponins; water content 14,915% ± 3,789; shrinkage in drying 29.105% ± 1.763; specific gravity 1.04 g / ml ± 0.0023. Extracts based on standardization testers include specific and non-specific parameters taking care of standardization of raw material quality.